(untitled) (Journal of Computational Mathematics, 2020)
The goal of this paper is to present a numerical method for the Smoluchowski equation, a drift-diffusion equation on the sphere, arising in the modelling of particle dynamics. The numerical method uses radial basis functions (RBF). This is a relatively new approach, which has recently mainly been used for geophysical applications. For a simplified model problem we compare the RBF approach with a spectral method, i.e. the standard approach used in related physical applications. This comparison as well as our other accuracy studies shows that RBF methods are an attractive alternative for this kind of models.